Relationship of serum adiponectin and resistin to glucose intolerance and fat topography in south-Asians - Barnett A H; McTernan Phillip G; Chetty Raja; Al-Daghri Nasser M; Wasim Hanif; Kumar Sudhesh (Cardiovascular Diabetology, 2006)
Abstract Objectives South-Asians have lower adiponectin levels compared to Caucasians. It was not clear however, if this intrinsic feature is related to aspects of glucose metabolism. This study aims to determine the relationship between body fat distribution and adipocytokine in South-Asian subjects by measuring serum adipocytokines, adiposity, insulinemia, and glucose tolerance levels. Methods In this cross-sectional study, 150 South-Asians (80 males, 70 females) were included, 60 had NGT (Control group, Age 51.33 ± 11.5, BMI 27 ± 2.3), 60 had IGT (Age 57.7 ± 12.5, BMI 27.2 ± 2.7), 30 had type 2 DM (Age 49.5 ± 10.9, BMI 28 ± 1.7). Measures of adiposity, adipocytokines and other metabolic parameters were determined. Parameters were measured using the following: a) Plasma glucose by glucose oxidase method b) CRP by immunoturbidimetric method (Roche/Hitachi analyser) c) insulin by Medgenix INS-ELISA immunoenzymetric assay by Biosource (Belgium) d) Leptin, Adiponectin by radioimmunoassay kits by Linco Research (St. Charles MO) e) Resistin by immunoassay kits by Phoenix Pharmaceuticals INC (530 Harbor Boulevard, Belmont CA 94002, USA). Results Adiponectin concentrations were highest in NGT, decreased in IGT and lowest in DMT2, (both p < 0.01). Leptin was significantly higher in DMT2 than IGT and NGT p = 0.02 and 0.04 respectively. There was a significant positive relationships between log adiponectin and 2-hr insulin values, p = 0.028 and history of hypertensions and a ischemic heart disease p = 0.008 with R = 0.65. There was a significant inverse correlation between log adiponectin and resistin, p < 0.01. Conclusion Resistin levels had an inverse correlation with adiponectin levels, indicating an inverse relationship between pro-inflammatory cytokines and adiponectin. Adiponectin levels were related to glucose tolerance.